Relationship between working capital management and profitability in Malaysian companies - Lee, Meng Yee (Universiti Malaysia Sarawak (UNIMAS), 2015)
Working capital management is a significant element in daily operation of a company. Working capital management had been a focus of various researchers and companies recently as it can be a guidance for financial manager in decision making so that every decision made can increase the value of the company. This study aim to investigate the effect of working capital management and profitability of Malaysian companies. In addition, this study also aim to investigate the relationship between working capital management and profitability. The sample size of this study is 80 listed companies from year 2009 until 2013. In order to fulfill the objective of this study, Pearson correlation coefficient, panel data analysis, Breusch test and Pagan Lagrangian Multiplier will be used. Based on the findings, there is a negative and significant relationship between number of days account receivable (ARD) and cash conversion cycle (CCC) with return on total assets (ROTA). However, number of days inventories (INV) and number of days account payable (AP) do not have significant relationship with return on total asset (ROTA).